Level of concentrate allocation and its effect on growth rate and feed utilization in mithun calves - PAL, D T; DUTTA, M; BUJARBARUAH, K M (The Indian Journal of Animal Sciences, 2014)
Production potentiality of mithun (Bas frontalis) under free range system of rearing has not so far been exploited to full extent due 10 restricted intake of nutrients from jungle. The growth rate of mit hun and its feed utilization at different levels of concentrate on tree forage based diets were studied. Mithun calves (12), weighing 167-177kg were divided into 2 groups and offered ad lib. tree forages and 2 different levels of concentrate (2kg, 4 kg/day/animal) for 5 weeks. Feed intake and growth rate were significantly increased with increase in concentrate level in the rations. Retention percentage of nutrients except CP, EE and ADF was improved on increase in supplementation of concentnlle. Energy value (TDN) of the ralion was higher and protein (DCP) remained similar in both the groups, which could be due to shortage of energy in lree forages.